Dose-Response Relationship Between External Load Variables, Body Composition, and Fitness Variables in Professional Soccer Players - Clemente, Filipe Manuel; Nikolaidis, Pantelis Theodoros; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2019)
The aim of this study was to test associations between accumulated external load and changes in body composition, isokinetic strength, and aerobic capacity of soccer players. Twenty-three professional soccer players (age: 24.7±2.8 years; height: 179.2±6.3; experience: 9.7±2.1 years) participated in this study. This pre-post study design was performed during 10 weeks from July to August of 2017 (4 weeks of pre-season and 6 weeks during the early season). Players were monitored daily by GPS technology and were assessed before and after a 10-week period in terms of body mass (BM), fat mass (FM), lean mass (LM), isokinetic strength at 60º/s, VO2max, and HRmax. Large-to-very large positive correlations were found between the sum of sprinting distance and % differences of BM (0.70, [-0.09;0.95]), HRmax (0.51, [-0.37;0.91]), agonist (quadriceps)/antagonist (hamstrings) left ratio (0.84, [0.27;0.97]) and agonist/antagonist right ratio (0.92, [0.58;0.99]). Large positive correlations were found between the acceleration sum and % differences of VO2max (0.58, [-0.29;0.92]), quadriceps left peak torque (0.66, [-0.16;0.94]), hamstrings left peak torque (0.68, [-0.13;0.94]) and hamstrings right peak torque (0.62, [-0.22;0.93]). Sprinting load was largely and positively associated with changes in knee strength asymmetries. Acceleration sum was largely and positively correlated with variations at VO2max and peak torques at hamstrings. In addition, dose-response relationships using external load variables were identified in professional soccer players.